'Drip-and-drive': shipping the neurointerventionalist to provide mechanical thrombectomy in primary stroke centers. (7th February 2018) - Brekenfeld, Caspar; Goebell, Einar; Schmidt, Holger; Henningsen, Henning; Kraemer, Christoffer; Tebben, Jörg; Flottmann, Fabian; Thomalla, Götz; Fiehler, Jens
Abstract : Background: To satisfy the increasing demand of mechanical thrombectomy (MT) for acute ischemic stroke treatment, new organizational concepts for patient care are required. This study evaluates time intervals of acute stroke management in two stroke care models, including one based on transportation of the interventionalist from a comprehensive stroke center (CSC) to treat patients in two primary stroke centers (PSC). We hypothesized that time intervals were not inferior for the 'drip-and-drive' concept compared with the traditional 'drip-and-ship' concept. Methods: Patients treated with MT at the PSC ('drip-and-drive', 'D+D group') were compared with patients transferred from PSC to CSC for MT ('drip-and-ship', 'D+S group') with regard to time delays. Time intervals assessed were: symptom onset to initial CT, to angiography, and to recanalization; time from initial CT to telephone call activation, to arrival, and to angiography; and time from telephone call activation to arrival and from arrival to angiography. Results: 42 patients were treated at the PSC after transfer of the interventionalist, and 32 patients were transferred to the CSC for MT. The groups did not differ with regard to median Onset–CT and CT–Phone times. Significant differences between the groups were found for the primary outcome measure CT–Arrival time ('D+D group': median 121 (IQR 108–134) min vs 181 (157–219) min for the 'D+S group'; P<0.001). Time difference between the groups increased to more than 2 hours for median CT–Angio times (median 123 (IQR 93–147) min vs 252 (228–275) min; P<0.001). Conclusion: Time intervals for the 'D+D group' were not inferior to those of the 'D+S group'. Moreover, under certain conditions, the 'drip-and-drive' concept might even be superior.